Monolithic interpretation of the Qur’an: revisiting selected verses on women - Khan, Mariya Seemin; Hashim, Rosnani (International Islamic University Malaysia, 2015)
Numerous Qur’anic verses such as 2:187, 4:19, 4:34, 7:189, and 30:21 deal with and address women, inspiring positively that women have serious role to play in the development of society. But it seems interpretation of these verses have been influenced by male chauvinism. Most of the Muslim scholars, early as well as contemporary, have tried to prove on the basis of these verses inferiority of womenfolk. This paper represents a humble effort to reflect on the related verses with a view to deriving positive messages rather than negative.